Validación de la Metodología de Evaluación de la Sostenibilidad Financiera a Organizaciones Textiles de Economía Popular y Solidaria, ciudad de Loja. - Estrada Ontaneda, Marco Elias (2023)
This study validates a Financial Sustainability measurement model by verifying its adaptability to the financial structure of textile organizations in the Popular and Solidarity Economy (PSE) in the city of Loja. To achieve this, three specific objectives were established: characterizing textile organizations, verifying the adaptability of a financial sustainability evaluation model to these organizations, and proposing sustainability strategies for financial and administrative management. Information was collected from registered textile organizations, and a survey was used to gather missing data and complete the necessary information. The evaluation model consists of four core dimensions: operating margin, capital structure, income diversification, and administrative expenses. Each dimension was evaluated on a 25-point scale and weighted according to the values established in the weighting table proposed by the author, with a maximum total score of 100 points. The results demonstrated that the combination of these four dimensions provides a comprehensive evaluation of financial sustainability in textile organizations of the PSE in the city of Loja. It is concluded that the model adequately adapts to the financial structure of these organizations and is valid for measuring their financial sustainability. Additionally, sustainability strategies are proposed to enhance financial and administrative management in these organizations.